Integrating Tinkering and Thinkering: an Effort to Break Practical Learning Myths - Agus Prianto; Nanik Sri Setyani; Ninik Sudarwati (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
This study describes the myth of practical learning in vocational school (VS) which is considered as a complement to learning activities. To break this myth, it requires a new perspective in understanding practical learning. Practical learning that combines tinkering and thinkering is expected to break the myth that has been going on for years. This study uses the Delphi method to summarize the results of studies by experts or previous researchers who have expertise related to the issues discussed, namely the myths of practical learning in VS. The opinions of experts or previous researchers are then used by researchers as a basis for making critical studies. The study revealed that practical learning can develop skills, expertise, proficiency that will lead graduates to become prospective workers at the employability level. Practical learning will also strengthen various soft skills that are needed by the world of work, such as: persistence in carrying out activities, never giving up, results-oriented, proactive, resilience, communicative, the ability to work in teams, and encouragement to continually update skills and expertise in harmony with the demands of the working world. Through practical learning, the students do not only memorize and understand concepts; but they will be conditioned to apply concepts, analyze practical activities, synthesis and evaluate the activities done. Thus, practical learning will familiarize students with high-order thinking. Practical learning is considered very effective in strengthening the spirit of tinkering and thinking of students in order to prepare candidates for employability-level workers. Practical learning will be able to deliver students as prospective workers who are not only smart, but also agile. This study recommends that practical learning is used as the main learning approach in VS, so that students are accustomed to be tinkering as well as thinkering so that they become candidates for employability level worker